Shadow Management and Corporate Criminal Liability in the Palm Oil Export Controversy in Indonesia - Martono Anggusti; July Esther; Budiman NPD Sinaga; Monalisa Marta Siahaan; Alex Denischael Berutu (Journal of Law, Politic and Humanities, 2026)
The development of corporate criminal law in Indonesia demonstrates the need to reconstruct the criminal liability model, which has tended to be oriented towards the formal structure of the company. In law enforcement practice, the determination of those responsible for corporate crimes is generally still based on the formal position of directors, even though in reality, strategic corporate decision-making does not always rest with those administratively listed as managers. This issue becomes increasingly relevant in the case of palm oil exports, particularly those related to Crude Palm Oil (CPO). Palm Oil (CPO), High AC ID Palm Oil Residue (HAPOR), and Palm Oil Mill Effluent (POME), which involves not only product classification and fiscal obligations, but also the identification of the parties who actually control corporate activities. This study aims to analyze the provisions on corporate criminal liability in Indonesian positive law, examining the relevance of the concept of effective control in determining the subject of corporate criminal liability, as well as formulating a reconstruction model of corporate criminal liability that is more in line with the development of modern corporate governance. This research is a normative legal research using a statutory approach, a conceptual approach, and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials analyzed qualitatively using descriptive-analytical and prescriptive methods. The results of the study indicate that the formalistic approach in attribution of corporate criminal liability has limitations because it is not always able to identify parties who have real control over corporate decision-making. The phenomenon of shadow management indicates the possibility that the party that actually controls the corporation is outside the formal structure of the company. Therefore, the concept of effective Control becomes a more relevant instrument for determining criminal liability by emphasizing a person's actual ability to control a company's policies, operations, and economic benefits. This study concludes that the ideal model for corporate criminal liability is a hybrid model that integrates the company's formal structure with testing of factual control (effective control). control), so as to be able to realize legal certainty, benefit, and justice in enforcing corporate criminal law, especially in cases of CPO, HAPOR, and POME exports.